Factors associated with breastfeeding maintenance for 12 months or more: a systematic review - Géssica S. Santana; Elsa Regina J. Giugliani; Tatiana de O. Vieira; Graciete O. Vieira (Jornal de Pediatria, 2018)
Objective: Synthesize the information about the factors associated with maintenance of breastfeeding for 12 months or more. Data source: A systematic review was conducted in the Pubmed/Medline, Scielo, and Lilacs databases, including articles published in Portuguese or English since 2004 on the factors associated with breastfeeding maintenance for at least 12 months; review articles and those with qualitative design were excluded. The factors were organized into four levels, according to the chronological proximity to the outcome: distal, distal intermediate, proximal intermediate, and proximal; nationality and place/area of residence were considered contextual factors. Summary of data: 1174 articles were identified, of which 19 were included in this review, comprising seven cohort studies and 12 cross-sectional studies. A total of 39 of the 75 assessed factors were associated with the outcome at least once. The factors with the highest percentages of associations with maintenance of breastfeeding for 12 months or more, considering the number of times they were tested were: children whose parents are the caregivers (100%), none type of maternal exposure to smoke (54%), children and/or parents are immigrants/foreigners (50%), live in urban areas (42.9%), older maternal age (40%), married women (37.5%), higher level of maternal education (31.3%), greater parity (30.8%), and lower income (30%). Conclusions: The maintenance of breastfeeding for 12 months or more is associated with multiple factors, emphasizing the contextual factors and those related to some maternal sociodemographic characteristics. Associations differ in effect and magnitude between the different populations studied. Resumo: Objetivo: Sintetizar as informações sobre os fatores associados à manutenção da amamentação por 12 meses ou mais. Fontes de dados: Foi conduzida revisão sistemática nas bases de dados Pubmed/Medline, Scielo e Lilacs, incluindo artigos publicados em língua portuguesa ou inglesa desde 2004 versando sobre fatores associados à amamentação por, no mínimo, 12 meses. Excluíram-se artigos de revisão e com delineamento qualitativo. Os fatores foram organizados em quatro níveis de acordo com a proximidade cronológica com o desfecho: distal, intermediário distal, intermediário proximal e proximal; nacionalidade e local/área de residência foram considerados fatores contextuais. Síntese dos dados: Identificaram-se 1.174 artigos, dos quais 19 foram selecionados para revisão, sendo sete estudos de coorte e 12 transversais. Dos 75 fatores explorados, 39 mostraram-se associados ao desfecho ao menos uma vez. Os fatores com os maiores percentuais de associações com a manutenção da amamentação por 12 meses ou mais, considerando o número de vezes que foram testados, foram: filhos terem os pais como cuidadores (100%), nenhum tipo de exposição materna ao fumo (54%), crianças e/ou pais serem imigrantes/estrangeiros (50%), morar em zona urbana (42,9%), maior idade materna (40%), mãe ser casada (37,5%), maior escolaridade materna (31,3%), maior número de filhos (30,8%) e menor renda familiar (30%). Conclusões: A manutenção da amamentação por 12 meses ou mais está associada a múltiplos fatores, com destaque para os fatores contextuais e os relacionados a algumas características sociodemográficas das mães. As associações diferem em efeito e magnitude entre as diferentes populações estudadas. Keywords: Review, Breast feeding, Epidemiologic factors, Palavras-chave: Revisão, Aleitamento materno, Fatores epidemiológicos